PENGARUH PEMBIAYAAN MODAL KERJA DENGAN AKAD MUSYA’RAKAH TERHADAP PROFITABILITAS BANK UMUM SYARIAH PERIODE 2016-2019 (STUDI KASUS PADA BANK MUAMALAT INDONESIA, BANK MEGA SYARIAH, BANK BCA SYARIAH) - Wahyu Wahyu; Sari Utami (Institut Agama Islam Negeri Bone, 2021)
Sharia financial performance is currently quite good. The higher the profit obtained by Islamic Banking, the better the performance of the bank. One way of Islamic banks in an effort to increase profit (profit) is to increase the source of fund income. The increase in sources of funds carried out by Islamic banks is by raising funds in the form of demand deposits, savings, deposits and channeling funds in the form of financing. This study discusses Islamic financial performance in the aspect of fund distribution, profitability is offered by using the ROA indicator, taken from working capital gains with Musyarakah contracts at three Islamic banks from 2016 to 2019. The approach used in this study discusses financial performance. The data used in this study is secondary data. This secondary data is obtained through the financial statements of Islamic Commercial Banks. The data required is the amount of Musyarakah financing, total profit sharing financing, net income and total assets. The data collection technique used in this research is documentation. The documentation used is in the form of financial statements of Islamic Commercial Banks consisting of three banks, namely Bank Muamalat Indonesia, Bank MEGA Syariah and Bank BCA Syariah through the website of the Financial Services Authority (OJK). The proposed variables have an effect on Profitability in Islamic Commercial Banks, namely: Is Working Capital Financing with Musyarakah (X) contracts. It turns out that it is not proven on the profitability of Islamic Commercial Banks (Y) in the long term, meaning that the hypothesis proposed on this matter is not proven. This means that in the long term Working Capital Financing with Musyarakah contracts does not affect the profitability of Islamic Commercial Banks (Bank Muamalat Indonesia, Bank MEGA Syariah, Bank BCA Syariah). However, in the short term it has the potential to be proven, meaning that in the short term Working Capital Financing with Musyarakah contracts has the potential to affect the profitability of Islamic Commercial Banks (Bank Muamalat Indonesia, Bank MEGA Syariah, Bank BCA Syariah).